PENGARUH TEKNOLOGI INFORMASI DAN PENGENDALIAN INTERNAL TERHADAP KINERJA INSTANSI PEMERINTAH - MZ, Era Inziaj; Yuliarti, Norita Citra; Aulin, Gardina (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Situbondo Regency, which is located in Situbondo City at the easternmost tip of East Java Province, was established in 1972 and adopted the motto "Bumi Sholawat Nariyah" (Land of the Living Gods) as its official slogan. Awards such as the Top Leader on Digital Implementation award, Top Digital Implementation Level Stars 4, and Top CIO on Digital Implementation at the 2021 Top Digital Awards show that Situbondo Regency is able to spread its wings and fly so far. Information technology is a major factor affecting government efficiency. Information technology refers to the practice of using technological resources effectively. When properly planned and implemented, IT- supported information systems can increase firm value (Nasir and Oktari, 2011). The government's efforts to establish a statewide tertiary information management system and network linking institutions with similar IT infrastructure are mandated by Section 79 of the Rhode Island Act No. 12 of 2012 concerning the Development of Higher Education. There can be no growth, accountability or transparency in government without the use of information technology to facilitate the generation and processing of data with greater speed and efficiency. The second thing that influences organizational performance is internal control.